Analisis Perlakuan Akuntansi pada Aset Bersejarah: (Studi Kasus pada Museum Negeri Provinsi Nusa Tenggara Barat) - Ovan Ferjiant; Elin Erlina Sasanti; Nungki Kartikasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to analyze the accounting treatment of historical assets in case studies at the state Museum of West Nusa Tenggara Province based on compliance with government regulations. This study employs descriptive qualitative methods, as well as data collection techniques such as interviews and documentation. The result of this study indicate that in defining historical assets in accordance with the meaning of these historical assets, and the recognition of historic assets is in accordance with Government Accounting Standards number 07 of 2010 in terms of the economic benefits provided by these assets. Valuation of historic assets at the state Museum of West Nusa Tenggara Province has not determined which methods to use, but the value is written in the financial statements in accordance with the acquisition. In terms of presentation and disclosure of historical assets in financial statements where the presentation of these historical assets is presented in the form of quantity only without value, and for disclosure to CaLK every year. Based on research conducted, accounting practices applied to the State Museum of West Nusa Tenggara Province are not fully in accordance with applicable government accounting standards.